2023
DOI: 10.14502/tekstilec.65.2022072
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner Production of Bioactive and Coloured Cotton Fabric Using Euclea Divinorum Dye Extract with Bio-Mordants

Abstract: Coloured textile products are more marketable, and are therefore always in higher demand. This has increased the use of synthetic dyes in the textile industry, thus raising environmental pollution associated with synthetic dyes. Natural dyes have been shown to be suitable alternatives. However, the use of metallic mordants during dyeing means the process is not eco-friendly, hence the need to develop bio-mordants that can be used as alternatives to some toxic metallic mordants. In this study, the effects of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been reported that colors in brown tones are obtained depending on the mordant substance. In one study, the effects of bio-mordants on the dyeing qualities of Euclea divinorum Hiern (Ebenaceae) dye extract were evaluated using several mordanting techniques on cotton fabric, according to Manyim et al (2023). For cotton fabric that has been dyed, the bio-mordants increased the color strength from 0.612 to 0.863 and 0.911 for mango and rosemary, respectively.…”
Section: Mango (Mangifera Indica L) Tree Barkmentioning
confidence: 99%
“…It has been reported that colors in brown tones are obtained depending on the mordant substance. In one study, the effects of bio-mordants on the dyeing qualities of Euclea divinorum Hiern (Ebenaceae) dye extract were evaluated using several mordanting techniques on cotton fabric, according to Manyim et al (2023). For cotton fabric that has been dyed, the bio-mordants increased the color strength from 0.612 to 0.863 and 0.911 for mango and rosemary, respectively.…”
Section: Mango (Mangifera Indica L) Tree Barkmentioning
confidence: 99%